Comprehensive assessment of risk factors and constant load monitoring prevent overuse injuries of extensor mechanism in elite volleyball players - Kara, Ö.; Kütük, E.; Akay, B.; Can, M. E. (British Journal of Sports Medicine, 2021)
Background Overuse injuries of extensor apparatus are common and debilitating in elite volleyball. Addressing the internal risk factors and monitoring the training load are key for injury prevention.